Indonesian Nationalism Facing Global Globalization - Arios, Rion; Kusbianto, Kusbianto (Universitas Dharmawangsa, 2022)
This paper contains that nurturing the spirit of nationalism in the minds of the younger generation since childhood will make them more resilient to negative influences and rampant moral change in the era of globalization. So, by strengthening morality and ethics through Pancasila Education, Indonesia's young generation will be better prepared to face globalization and maintain Indonesian identity at the same time. Cultural values that are characteristic of the Indonesian nation, such as mutual cooperation, silahturahmi, hospitality in the community become basic privileges that can make individuals of Indonesian society to love and preserve their own national culture. But the characteristics of the Indonesian people who are known as a friendly society and manners are now beginning to fade since the entry of foreign culture into Indonesia that can not be selected properly by the people of Indonesia. Therefore, in this case the government has an important role to maintain the values of Indonesian culture in the lives of its people. The following are some ways to maintain Indonesian culture so as not to be affected by foreign cultures that are negative, 1) foster a strong spirit of nationalism, such as the spirit of loving domestic products and culture. 2) instill and practice the values of Pancasila as well as possible. 3) instill and implement religious teachings with the best. 4) selective against foreign cultures entering Indonesia. 5) strengthen and maintain the identity of the nation so as not to fade. That way the community can act wisely in determining the attitude so that the identity and personality of the nation does not fade because of foreign cultures that enter Indonesia in particular.